Police–Community Relations: Strengthening Trust, Collaboration, and Public Safety Outcomes - Veronica Ari Herawati (Universitas Negeri Semarang, 2025)
Police–community relations play a critical role in shaping public trust, ensuring democratic accountability, and improving the effectiveness of law enforcement. This study examines the dynamics between police institutions and communities by assessing levels of trust, communication quality, participation in policing programs, and responsiveness to public concerns. Using a mixed-methods approach involving survey data from 1,250 respondents, structured interviews with police officers and community leaders, and field observations, the study identifies key determinants that influence public perceptions of policing. Quantitative findings reveal that transparent communication and community engagement initiatives significantly predict trust levels (p < 0.01), while qualitative insights highlight persistent challenges such as unequal service distribution and limited public participation in decision-making. Results indicate that collaborative policing programs contribute to reductions in neighborhood disputes, increased reporting rates, and enhanced legitimacy of police actions. The study concludes that strengthening police–community relations requires sustainable engagement strategies, institutional reforms promoting accountability, and the integration of community feedback into operational planning. The research contributes to policing science by offering an evidence-based framework for improving social cohesion, enhancing public safety outcomes, and increasing institutional legitimacy.